"Knabenkopf"; Portrait eines Knaben, eine Postkarte des SAH
internationale Politik (allgemein);internationale Beziehungen;Entwicklungszusammenarbeit;Hilfswerk soziale Fragen;sozialer Schutz;Sozialhilfe